The influence of socio-cultural features in the contents of delusions, football delusion – Two Clinical cases - Caseiro, João (2018)
We describe the clinical cases of two 17 year-old patients presenting a first psychotic episode in which football was central to their delusional beliefs. These two patients were admitted with a five-month’s gap in an inpatient clinic after the intervention of the authorities who conducted them to the emergency room. Football has become the main global mass entertainment phenomenon of the contemporary European society. Therefore, it’s not surprising that in the year that Portuguese football had its most glorious moment with the Euro Cup victory, the game took part in the delusional beliefs of two young people presenting their first psychotic episode. With the description of these two clinical cases we intend to emphasise on the relation between socio-cultural features and the content of the delusional beliefs.